2021
DOI: 10.1002/ddr.21794
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cyclooxygenase enzyme for the adjuvant COVID‐19 therapy

Abstract: Despite vigorous efforts, the COVID‐19 pandemic continues to take a toll on the global health. The contemporary therapeutic regime focused on the viral spike proteins, viral 3CL protease enzyme, immunomodulation, inhibition of viral replication, and providing a symptomatic relief encouraged the repurposing of drugs to meet the urgency of treatment. Similarly, the representative drugs that proved beneficial to alleviate SARS‐CoV‐1, MERS‐CoV, HIV, ZIKV, H1N1, and malarial infection in the past presented a sturdy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Our recommendation treatment algorithm (17) is based on the idea that it is critical to intervene at home very early on during the onset of mild/moderate symptoms to avoid progression toward severe COVID-19, which would eventually require hospital admission. Indeed, after the initial exposure to SARS-CoV-2, patients typically develop symptoms that indicate an inflammatory process within 5 to 6 days on average (15,16), and pro-inflammatory mediators, in particular cytokines, seem to be integral to the initiation, intensification, propagation and worsening of tissue morbidity related to COVID-19 (16,19,26). Therefore, our recommended treatment algorithm moved from this pathophysiologic rationale of early COVID-19 events, and focused on the initial use of NSAIDs, which has been shown to reduce pro-inflammatory cytokine levels (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recommendation treatment algorithm (17) is based on the idea that it is critical to intervene at home very early on during the onset of mild/moderate symptoms to avoid progression toward severe COVID-19, which would eventually require hospital admission. Indeed, after the initial exposure to SARS-CoV-2, patients typically develop symptoms that indicate an inflammatory process within 5 to 6 days on average (15,16), and pro-inflammatory mediators, in particular cytokines, seem to be integral to the initiation, intensification, propagation and worsening of tissue morbidity related to COVID-19 (16,19,26). Therefore, our recommended treatment algorithm moved from this pathophysiologic rationale of early COVID-19 events, and focused on the initial use of NSAIDs, which has been shown to reduce pro-inflammatory cytokine levels (18).…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs inhibit the cyclooxygenase activity of prostaglandin H synthase 1 and 2, also named COX-1 and COX-2 (27). Relatively selective COX-2 inhibitors (e.g., celecoxib, etoricoxib) (27) may reduce pro-inflammatory cytokine levels, as shown in mice with influenza A infection (TNF-α, G-CSF, and IL-6) (28) and in hospitalized COVID-19 patients (IL-6) (19,29). The overlap in COX-2 selectivity between coxibs and the more traditional NSAID nimesulide (27) was the rationale for recommending these drugs for the treatment of early COVID-19 at home, unless contraindicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection also upregulates COX-2 in human cell culture and mouse models [ 7 ]. The effectiveness of COX-1/COX-2 inhibition by non-steroidal anti-inflammatory drugs (NSAIDs) such as naproxen and celecoxib, discouraging the inflammasome activation could limit the cytokine storm [ 8 ]. Although it was initially suggested that NSAIDs could increase ACE2 receptor expression, thereby possibly promoting viral entry, a recent clinical trial attested the safety of COX-2 inhibitors and suggested their ability to reduce IL6 levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drugs with potential for inhibiting these overexpressed immunogenic pathways in the tissues invaded by coronaviruses has been a matter of debate since the inception of the pandemic. The effectiveness of NSAIDs such as Indomethacin in COVID-19 coagulopathy, discouraging the SARS viral replication, the inflammasome deactivation, and synergistic inhibition of H5N1 viral infection with representative antiviral drugs, have provided a silver lining in adjuvant COVID-19 therapy [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%